A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil - Soares, Matheus M. M.; Barros, Luana M.; Ale-Rocha, Rosaly (Zootaxa, 2020)
We report for the first time the occurrence of genus Micropeza from Caatinga biome, through the description of M. chiroptera sp. nov. The new species is probably closely related to M. dactyloptera Harterreiten-Souza, Sujii & Pujol-Luz, 2014 by the finger-shaped projection on costal vein. A key of Micropeza species with a finger-shaped projection on costal vein and a distribution map of these species are provided.